Kontribusi al-Madrasah al-Amīriyyah al-Islāmiyyah Watampone Terhadap Pendidikan Islam di Bone - bakar, abu (JURNAL AL-QAYYIMAH, 2020)
This thesis studies about contribution of an Islamic education institution which has existed since the 32nd Raja Bone Andi Mappanyukki Sultan Ibrahim, that is al-Madrasah al-Amīriyyah al-Islāmiyyah Watampone. The main problem is how the role/contribution of this madrasah to the Islamic education in Bone. This problem is seen with a pedagogical historic approach and discussed by using qualitative method with descriptive analysis.Al-Madrasah al-Amīriyyah al-Islāmiyyah Watampone is built in 1933 by raja and theologian with the public figure at the time. Along with time this madrasah is renamed to Sekolah Menengah Islam (SMI), then become PGA, and now it becomes SMA Amir Islam Watampone which is located at Jl. Sungai Kapuas No. 6 Kecamatan Tanete Riattang, Kabupaten Bone. The curriculum which is used at the Ibtidaiyah level is 50% general science and 50% theology, at the Tsanawiyah level is 60% theology and 40% general science, whereas at the Muallimin level, it is taught 80% theology and 20% general science. This Madrasah has contributed to the Islamic Education in Bone, it is creating alumni who have contribution in the middle of society. Beside that, this Madrasah has contributed to the building of MAN 2 Bone which is PGA 6 Tahun that is renamed to MAN 2 Bone. Furthermore, PGA 4 Tahun becomes MTsN Wajo and STAI al-Gazali has done the learning in this madrasah. The madrasah also publishes certificate/evidence that they have participated in training for the priest village as a Kadi helper. Therefore, it can be concluded that this madrasah has given much contribution to the progress of Islamic education in Bone even outside Bone. However to be more perfect, this thesis needs follow-up in the field related to the data that has been found.